Informality and Regulations : What Drives Firm Growth? - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2007)
The paper relies on a rich firm-level data set on transition economies to examine the role of informality as an important channel through which regulatory and other policy constraints affect firm growth. We find that firms reduce their formal operations with a higher tax and regulatory burden, but increase it with better enforcement quality. In terms of firm growth, we find a differential impact of regulatory burden and enforcement quality on formal and informal firms. In particular, we find that growth in formal firms is negatively affected by both tax and financing constraints, while these constraints are insignificant for growth in informal firms. Moreover, formal firm growth improves with better enforcement as measured by fair and impartial courts, while informal firm growth is constrained by organized crime, pointing to their inability to take full advantage of the legal and judicial systems. Finally, when we look at country-wide institutions, we find that higher regulatory burden reduces firm growth. An interactive term between a country-wide measure of the rule of law and a proxy for formality suggests that better enforcement quality dampens the relatively weaker growth in formal firms.